1979
DOI: 10.1002/eji.1830091215
|View full text |Cite
|
Sign up to set email alerts
|

Surface Ig on rabbit lymphocytes Rabbit B and T cells are distinct populations

Abstract: Rabbit peripheral blood lymphocytes (PBL) were analyzed by immunofluorescence using anti-T cell conjugates and anti-Fab, anti-a1 allotype, anti-IgM and anti-IgA conjugates. In addition, T cells were demonstrated by rosetting with papain-treated homologous erythrocytes. Control experiments, using acid treatment and incubation at 37 degrees C for 18 h after or without pronase treatment, revealed the endogenous origin of all surface determinants tested. A good correlation was found between results obtained with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

1980
1980
1982
1982

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 39 publications
2
4
0
Order By: Relevance
“…Our data are compatible with those of others, who showed, using fluorescence microscopy, that rabbit B and T cells are distinct subpopulations [13,15,[27][28][29][30].…”
Section: Discussionsupporting
confidence: 96%
“…Our data are compatible with those of others, who showed, using fluorescence microscopy, that rabbit B and T cells are distinct subpopulations [13,15,[27][28][29][30].…”
Section: Discussionsupporting
confidence: 96%
“…It has also been reported that (a) the anti-VH 315 antibodies (16) inhibit T cell function in mice (17)(18)(19) and cross-react with antigen-specific, soluble factors of T cells (20, 21) (b) unabsorbed chicken antisera against human V/~ fragments stain by immunofluorescence ~30% of normal T cells (44), and (c) unabsorbed rabbit antibodies against the VH fragments of a human IgG3~ myeloma also show weak reactivity by immunofluorescence with ~20% of normal T cells and may inhibit mixed lymphocyte reactions (45). In contrast, our monoclonal anti-Vn antibodies appear unreactive by immunofluorescence with either surface or cytoplasmic components of both resting and activated T cells, and this is consistent with the results of others using goat anti-VH subgroup antibodies (48), rabbit anti-VH framework antibodies (42), and rabbit VH allotype antibodies (11)(12)(13)(14)(15). Our monoclonal anti-Vn subset antibodies could be valuable reagents in the future analysis of this issue using very sensitive assays of antigen-specific, soluble factors of murine and human T cells.…”
Section: Discussionsupporting
confidence: 92%
“…One set of goat antibodies specific for each human VH subgroup has been prepared by selective adsorption and was found to be useful in typing secreted and membranebound Ig on B cells (3).Evidence from studies (4-8) using anti-idiotype antibodies has suggested that T cells and their antigen-specific, soluble factors might possess Ig-like idiotypic determinants. VH allotypic determinants have also been demonstrable on rabbit T cells by several groups (9, 10) and not by others (11)(12)(13)(14)(15). Antibodies against VH framework regions of the mouse myeloma protein MOPC-315, which cross-react with other mouse Ig regardless of their antibody specificity, class, subclass, subgroup, or allotype (16), may inhibit T cell function (17)(18)(19) and cross-react with soluble factors ofT cells (20,21).…”
mentioning
confidence: 99%
“…The content of nonlymphoid cells in isolated rabbit PBL suspensions varies, depending on the isolation procedure [39]. Differentiation of the RFC with respect to their morphological characteristics, and, within the lymphocytes, their T, B or null cell features, is described in the following report [23].…”
Section: Discussionmentioning
confidence: 99%
“…a) The percentages of EAy RFC, IgM-positive cells (F(ab')2 antiIgM-TRITC [39]) and complement-rosetting leukocytes (RL) [25] were determined in untreated PBL (U), immediately after pronase treatment (P), after incubation (I) during 18 h at 3 7 T , and after pronase treatment followed by 37°C incubation (PI). The percentages are expressed as percentage from the initial values, which varied .…”
Section: ? 17mentioning
confidence: 99%